High stakes - Michaels, Fern (Michaels, Fern. Men of the Sisterhood., 2017)
Investigative reporter Dennis West joined forces with the men of the Sisterhood to help fight corruption and greed on behalf of underdogs everywhere. Now he and his band of brothers are on a mission to help an old friend in danger: Toby Mason was a whip-smart college nerd - nothing like the buff dancer at the Supper Club who's reached out to Dennis. The owners of the Supper Club adult-entertainment franchise have expanded their empire through tours, contests, and calendars. But Toby suspects the Supper Clubs offer a convenient front for a major drug trafficking operation - and those suspicions have become known to his employers. At the top-secret headquarters of BOLO Consultants, Dennis, Jack, Abner, Ted, Harry, and the rest of the crew gather to formulate a plan. It'll mean going deep undercover, but the men of the Sisterhood are breaking out their most impressive moves to stop a criminal network that's stayed two steps ahead of justice for too long.